(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
In addition to the risks faced by traditional financial institutions, Islamic banks are widely exposed to sharia-related risks with regards to the need for ensuring compliance of its operational activities and financial products with Islamic law. In order to mitigate these additional risks, Islamic financial institutions are urged to establish a comprehensive ’Framework for Sharia Risk Management’ that can help them monitor their banking, financing and investment activities in conformity with sharia principles and hence enhance their sustainability in the long run. Keywords: Sharia Risk Management Practices, sharia compliant, Islamic finance, traditional financial institutions, banking system